2023
DOI: 10.3390/pathogens12030496
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Macrolide and Fluoroquinolone Resistance in Mycoplasma genitalium and Their Prevalence in Moscow, Russia

Abstract: Macrolide (MLR) and fluoroquinolone (FQR) resistance in Mycoplasma genitalium (MG) has recently become a major problem worldwide. The available data on the prevalence of MLR and FQR in MG in Russia are limited. In this study, we aimed to evaluate the prevalence and pattern of mutations in 213 MG-positive urogenital swabs from patients in Moscow between March 2021 and March 2022. MLR- and FQR-associated mutations were searched in 23S rRNA as well as in the parC and gyrA genes using Sanger sequencing. The preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…As in other studies ( 22 , 23 ), the gyr A locus in M. genitalium is remarkably well conserved in our population also (e.g., only two samples have exhibited amino acid substitutions in gyr A, both with uncertain significance), and none of the 10 nonsynonymous mutations in gyr B identified in this study were previously published. Thus, in our setting, as described in other works, parC appears to be the major determinant for fluoroquinolone resistance, while the contribution of gyrase loci may be considered minor.…”
Section: Discussionsupporting
confidence: 87%
“…As in other studies ( 22 , 23 ), the gyr A locus in M. genitalium is remarkably well conserved in our population also (e.g., only two samples have exhibited amino acid substitutions in gyr A, both with uncertain significance), and none of the 10 nonsynonymous mutations in gyr B identified in this study were previously published. Thus, in our setting, as described in other works, parC appears to be the major determinant for fluoroquinolone resistance, while the contribution of gyrase loci may be considered minor.…”
Section: Discussionsupporting
confidence: 87%
“…From a genetic vantage point, macrolide resistance primarily arises from a single base mutation, typically occurring at position A2058 or A2059 within region V of the 23S rRNA gene (according to Escherichia coli numbering) [19,20]. On the other hand, resistance to fluoroquinolones is associated with mutations found in the quinolone resistance-determining region (QRDR) of the parC gene, often resulting in amino acid substitutions at positions S83 and D87 (according to M. genitalium numbering) [19,20]. Nonetheless, the existing data supporting correlations between mutations in parC and clinical resistance to moxifloxacin are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the existing data supporting correlations between mutations in parC and clinical resistance to moxifloxacin are limited. It has been suggested that mutations in the QRDR of the gyrA gene in isolates exhibiting a fluoroquinolone-resistant genotype in parC may enhance the likelihood of reduced susceptibility to fluoroquinolone antimicrobials [19,20]. Nonetheless, the confirmation of such claims without phenotypic data poses a significant challenge in understanding the intricacies of fluoroquinolone resistance in M. genitalium infections.…”
Section: Discussionmentioning
confidence: 99%